Soybean DNA extraction from blended refined vegetable oils - Costa, Joana (2010)
The major genetically modified (GM) crop species is soybean (Glycine max), accounting for 53% of the total world’s GM planted area and 70% of the soybean annual production in 2008 [1]. Since the approval of Roundup Ready® (RR) soybean in EU, the production of soybean oil using GM seeds has been increasing. In EU, the doubts raised by the use of genetically modified organisms (GMO) lead to the mandatory labelling for food products containing more than 0.9% of authorised GMO. In blended edible oils prepared with mixtures of two or more different oils, it is important to verify the labelling statements concerning their constituents and the presence of GM material, since soybean oil is frequently used. The analysis of DNA coupled with polymerase chain reaction (PCR) has been the technique of choice to monitor the presence of GMO in food. However, it is very difficult to obtain amplifiable DNA from oil since most vegetable oils, like crude soybean oil, must be refined prior to its consumption.